Kinetic control of CeO2 nanoparticles for catalytic CO oxidation. Issue 13 (15th July 2019) - Han, Bingqi; Li, Huixia; Li, Liping; Wang, Yan; Zhang, Yuelan; Li, Guangshe
Abstract: Abstract : This article reports on the growth kinetics of cerium oxide (CeO2 ) nanoparticles prepared via a sintering method. By varying the sintering temperatures and periods of time, particle size of CeO2 nanoparticles was tuned from 11 to 100 nm. Ostwald ripening mechanism prevails in the growth process, and the growth kinetics is determined to follow an equation, D 5 = 16.2 5 + 3.6 × 10 20 exp(−344.20/ RT ) in the temperature range of 700 to 1000°C. After dispersing Pt on CeO2 nanoparticles, the size effect for the catalytic performance of the CO oxidation reaction was researched. When temperature and period of time are set at 700 °C and 2 h, respectively, dispersion of Pt onto CeO2 nanoparticles led to the largest quantity of chemisorbed oxygen species on the surface and the best catalytic performance. The findings reported here would provide a feasible path for the preparation of advanced catalysts in the future and moreover to discover novel size-dependent supports for many catalytic applications.